1990
DOI: 10.1055/s-2008-1053568
|View full text |Cite
|
Sign up to set email alerts
|

Die Liquorgängigkeit von Ofloxacin (Tarivid®) bei nicht entzündeten Meningen*

Abstract: In 9 patients, who underwent lumbar drainage after transsphenoidal surgery for pituitary adenoma, we collected 69 samples of CSF and plasma, respectively. The concentration of ofloxacin was measured bacteriologically. Considering the ofloxacin CSF and plasma levels related to time some aspects of pharmacokinetics are discussed. With maximum CSF concentrations coming up to 40% of plasma levels liquor penetrability is quite good. Ofloxacin seems to be able to prevent (postoperative) meningitis, even with grampos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…A nonlinear plasma-CSF transit dependent on the concentration of drug in plasma has been observed with ciprofloxacin in rats, which may have been caused by a carrier-mediated transport from CSF to blood (8). In contrast, the CSF ofloxacin concentrations measured in the present study were approximately twofold greater than those found after administration of the first dose of 200 mg to subjects with uninflamed meninges (2,20); i.e., at doses of 200 and 400 mg, passage from serum to CSF was approximately linear in humans.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…A nonlinear plasma-CSF transit dependent on the concentration of drug in plasma has been observed with ciprofloxacin in rats, which may have been caused by a carrier-mediated transport from CSF to blood (8). In contrast, the CSF ofloxacin concentrations measured in the present study were approximately twofold greater than those found after administration of the first dose of 200 mg to subjects with uninflamed meninges (2,20); i.e., at doses of 200 and 400 mg, passage from serum to CSF was approximately linear in humans.…”
Section: Discussioncontrasting
confidence: 49%
“…In subjects with inflamed and uninflamed meninges, ready passage of ofloxacin into the cerebrospinal fluid (CSF) has been observed after administration of an oral or intravenous (i.v.) dose of 200 mg (2,15,20,21). The concentrations in CSF were, however, not high enough to be relied upon for use in treating central nervous system (CNS) infections caused by the staphylococci predominantly involved in ventriculitis (2,15,20,21 Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation